Effects of Dietary Probiotic Bacillus sp. D2.2 and Prebiotic Sweet Potato Extract on Growth Performance and Resistance to Vibrio harveyi in Pacific white shrimp, Litopenaeus vannamei - Harpeni, Esti; Santoso, Limin; Supono, Supono; Wardiyanto, Wardiyanto; Widodo, Ari; Yolanda, Laksmita (Aquacultura Indonesiana, 2017)
In this study, the effects of oral administration of probiotic Bacillus sp. D2.2 and prebiotic from sweet potato extract on growth performance and resistance against Vibrio harveyi in Pacific white shrimp (Litopenaeus vannamei) were investigated. During 32-day feeding experiment, 360 individuals of Pacific white shrimp (PL15) with initial weight of 0.02 ± 0.002 g were fed with basal diet as control (A); supplemented with 6% probiotic and 0% prebiotic (B); 6% probiotic and 2% prebiotic (C); 6% probiotic and 4% prebiotic (D). At the end of feeding trial, weight gain (WG), average daily growth (ADG), feed conversion ratio (FCR), and survival rate (SR) were assessed. WG, ADG and FCR of the shrimp were significantly better in treatment D than those of the shrimp in other treatments. Control and treatment D as the best feeding trial were selected for challenge test with infectious V. harveyi. Survival rate and mean time to death (MTD) of the shrimp fed the supplemented diet were not significantly different (P>0.05) to the control. Infection levels in shrimp were evaluated using morphological scoring methods. Infection levels of V. harveyi in shrimp fed the diet were lower compared to the control.